THE ROLE OF THE KWASHE INDUSTRIAL ZONE IN THE SUMMEL DISTRICT BY POLLUTION ON THE SURROUNDING ENVIRONMENT - Khalil, Jiyan Suliman; Hassam, Ibrahim Khoshman (Journal of Duhok University, 2018)
The study aims at to study the role of the contaminated industrial area in Quashy in the Summel district and its contribution to the pollution of the surrounding environment, with the result of the industrial establishments of harmful effects resulting from the industrial processes and accompanying the process of production therein. This is done by studying the industrial structure of the industrial units in which the industrial industries (Construction, Plastic, Chemical, Mineral, Oil, Food, Wood, Paper, Electrical, Leather tanning and Textile industries) amounted to 161 factories. Vary in the degree of their harmful effects and polluting the environment according to the classification system of industrial pollutants for industry issued in the facts of Kurdistan for the Kurdistan Regional Government of Iraq. In addition, the most important factors influencing or assisting the pollution of the environment surrounding this industrial zone. On the basis of which we reached at the end of the study the harmful effects of industrial pollution on the surrounding environment.